After Sale Service and Relationship Marketing within Construction Equipment Excavator Segment in India: Expanding customer relationships in the construction equipment industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The demand for construction equipment is a reflection of broader macroeconomic trends such as interest rates, infrastructure investment and liquidity, which themselves indicate the health of the overall economy. The manufacturers are lining up new models and expanding production capacity to tap the coal sector market. The Indian market has witnessed entry of a number of multinational companies and, now competing with local. After sales service refers to various processes which make sure customers are satisfied with the products and services of the organization. After sales service plays an important role in customer satisfaction and customer retention and generates loyal customers. The major activities of after-sales success in the manufacturing industry, have been identified as field technical assistance, spare parts distribution and customer care. Service quality impacts on satisfaction, satisfaction on customer retention (customer loyalty), and customer retention has impact on profitability. Heavy the construction equipment companies are shifting their emphasis from original products sales to customer needs customers find value in the trouble-free operation of products. After Sales operations have a very broad scope and contain all activities related to maintaining a vehicle after its initial sale and until the end of its lifecycle. Spare parts distribution is responsible for inventory management, customer order management and delivery of spare parts. The relationship between a company and a customer had been formed on a product centric view. Presently, businesses this view has been changed and the aim is to focus on maintaining relationship with customers as there are values for both parties